Massive cortical reorganization is reversible following bilateral transplants of the hands: evidence from the first successful bilateral pediatric hand transplant patient. Issue 1 (6th December 2017) - Gaetz, William; Kessler, Sudha K.; Roberts, Tim P.L.; Berman, Jeffrey I.; Levy, Todd J.; Hsia, Michelle; Humpl, Deborah; Schwartz, Erin S.; Amaral, Sandra; Chang, Ben; Levin, Lawrence Scott
Abstract: In this repeated measures case study, we show that sensory deafferentation after limb amputation leads to changes in cortical somatotopic maps which are reversible after restoration of sensory input. Using magnetoencephalography (MEG), we observed in a child with bilateral hand transplants large‐scale shifts in somatosensory lip cortical representation from anatomic hand area to anatomic face region. After recovery of tactile sensation in the digits, responses to finger stimulation were localized to orthotopic sensory cortex, but with atypical electrophysiologic features (amplitude and frequencies).